Modeling and Analysis of Silicon Reflective-type Microring Resonator Assisted MZI as Filtering Device - El-edresee, Esraa; Al-mfrji, Alhuda A. (Al-Nahrain Journal for Engineering Sciences, 2024)
Recently microwave photonic filter (MPF) have a great interest due to their advantages which include low loss, wide bandwidth tunability, reconfigurability, and no electromagnetic interference. This paper presented a comprehensive optical transmission analysis of a reflective-type microring resonator (R-MRR) using coupled mode theory, and design guidelines for MPF through two cascaded R-MRR using COMSOL software simulation results. The design was implemented on silicon-on-insulator (SOI) platform-based MPF which exhibits wide bandwidth tunability and reconfigurability by adjusting the coupling coefficient in the two coupling regions. In this structure, a grating coupler (GC) reflector is introduced to the drop port of MRR. The analysis and simulation results were confirmed by utilizing a GC reflector and Mach-Zehender Interferometer (MZI). The results of the proposed MPF at laser light input of (1.55*10^6- m) wavelength showed the bandwidth and center frequency are adjusted from 0.3 to 6 GHz and 13 to 54.8 GHz, respectively, with a high rejection ratio reaching 70 dB. Overall, the structure represents a significant step towards designing the MPFs, which show perfect flexibility and have numerous applications in such fields as radar, sensor, and wireless communications.